2017
DOI: 10.1080/14649365.2017.1373145
|View full text |Cite
|
Sign up to set email alerts
|

A place in the sun? Discursive constructions of positive outcomes in post-migration stories in the Algarve

Abstract: This study argues for more comparative research between seemingly different migrant groups, bringing a new focus on intra-European migration in Portugal by examining and comparing the reasons why migrants from different geographical origins choose to settle in the tourism-based Algarve region. Drawing on data collected from a questionnaire survey and interviews, the study first compares the profiles of two apparently distinct migrant groups -Northern and Eastern Europeans -and goes on to explore their discursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…With a limited proficiency in the Portuguese language, or even adopting the practice of not speaking Portuguese, British migrants in densely populated coastal areas easily place themselves into a self-marginalised existence (Torkington, 2015). However, this does not prevent them of feeling that they belong to the place where they have chosen to live, depending on the time that is spent living in the region (Torkington & Perdigão Ribeiro, 2019), and German migrants in Western Algarve have also been shown to have similar feelings (Herbers, 2017).…”
Section: Knowledge Regarding How Eu Citizens Live and Integrate Intomentioning
confidence: 99%
“…With a limited proficiency in the Portuguese language, or even adopting the practice of not speaking Portuguese, British migrants in densely populated coastal areas easily place themselves into a self-marginalised existence (Torkington, 2015). However, this does not prevent them of feeling that they belong to the place where they have chosen to live, depending on the time that is spent living in the region (Torkington & Perdigão Ribeiro, 2019), and German migrants in Western Algarve have also been shown to have similar feelings (Herbers, 2017).…”
Section: Knowledge Regarding How Eu Citizens Live and Integrate Intomentioning
confidence: 99%
“…During the last 20 years, a lifestyle-related migration has emerged as a major migration type, alongside traditional labour market-related migration, refugee migration and tied movers (Vandermotten et al 2004;Haas 2011). The prospect of being a permanent tourist (O'Reilly 2007;Ibrahim & Tremblay 2017;Åkerlund 2015), retirement (Casado-Díaz 2006;Gustafsson 2009) and the feeling of affluence and being privileged (Janoschka & Haas 2013;Benson 2014) have stimulated, for example, French to Morocco (Therrien 2013;Therrien & Pellegrini 2015), Brits to France (Benson 2009(Benson , 2010(Benson , 2011(Benson , 2013b, Spain (O'Reilly 2000 and Portugal (Torkington 2010(Torkington , 2015Torkington & Perdigão Ribeiro 2019), Americans to Panama (Jackiewicz & Craine 2010;Benson 2013a) and Swedes to Spain (Gustafsson 2001;Olsson 2017;Woube 2017) and Malta (Åkerlund 2013Åkerlund & Sandberg 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One obstacle to integration that is almost always cited is the language barrier. Many studies have observed that inability to communicate in the local language is widespread (Torkington & Ribeiro 2019). The reasons listed for the creation and maintenance of this language barrier are always similar: participants report that it is not, after all, necessary to learn and use the local language to enjoy the "good life", including in the Algarve (Torkington 2015).…”
Section: Introductionmentioning
confidence: 99%